Support Student Engagement through Technology-Based Collaborative Platforms - Priyatno, Dwi; Wardhani, Rizky; Cheriani, Cheriani; Alfredo, Yoel Frans; Sabur, Fatmawati (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Keeping students engaged in teaching and learning activities is a very difficult task for teachers and schools. Changes in school systems are continuously changing the way students interact and engage in learning, forcing educators to explore resources and strategies to better support students. Educational technology helps educators meet today's needs and is an important resource for the learning process. Increased use of technology in learning environments can support and enhance student engagement. The emergence of collaborative platforms is a form of technological interest to support student engagement. The purpose of this research is to explore whether technology with collaborative platforms can support student involvement in the learning process. Through research on supporting student engagement through this technology-based collaboration platform, researchers hope that using technology-based collaboration platforms in learning can help students in the learning process. The method used in this research is a quantitative method. Researchers conducted a survey using a Google form consisting of 15 sentences related to the research title. The researchers found that supporting student engagement through technology-based collaborative platforms had a major impact on student engagement. The presence of a collaborative learning platform makes students more enthusiastic and excited. Students feel that with cooperation in the learning process, learning becomes more differentiated and attracts students' attention. The limitations of this research are that researchers only conduct research in schools and researchers do not conduct research directly in schools but share survey links on Google forms containing statements about supporting student engagement through technology-based collaborative platforms.